Profiles of older adults according to their life and food-related life satisfaction during the COVID-19 pandemic: the importance of the social environment - Berta Schnettler; Berta Schnettler; Berta Schnettler; Berta Schnettler; Germán Lobos; Ligia Orellana; Ligia Orellana; Ligia Orellana; Cristian Adasme-Berríos; María Lapo; Katherine Beroíza (Frontiers Media S.A., 2023)
IntroductionOlder adults are a highly heterogeneous population, as individuals of the same age can show considerable variations in personal characteristics and living conditions. Risk and protective factors for older adults' subjective wellbeing during the COVID-19 pandemic can be explored by examining how life satisfaction, food-related life satisfaction, and associated variables coexist among these individuals. On this basis, this study aimed to identify older adult profiles based on their levels of life and food-related life satisfaction; to characterize these profiles by diet quality, social support, financial wellbeing, and sociodemographic characteristics; and to identify variables associated with higher life and food-related life satisfaction.MethodsThe sample included 1,371 institutionalized and non-institutionalized individuals over the age of 60, from four cities in Chile. Participants answered a survey, either online or face to face, with questions about life and food-related life satisfaction, perceived social support from family, friends, and others, food quality, financial wellbeing/distress, sociodemographic characteristics, and prior COVID-19 infection.ResultsUsing a latent profile analysis, we identified three profiles of older adults: Profile 1: Unsatisfied with their life, somewhat satisfied with their food-related life (5.40%); Profile 2: Somewhat satisfied with their life, satisfied with their food-related life (65.06%); Profile 3: Extremely satisfied with their life and food-related life (29.54%). Profiles differed by residence (institutionalized vs. independent), age, marital status, social support, financial wellbeing, COVID-19 infection, and city of residence.DiscussionThe patterns of association between life and food-related satisfaction and related variables indicate conditions of vulnerability and protection related to living conditions, the social dimensions of food consumption, and social support. These results underscore the need for identifying groups of older adults based on diverse characteristics and conditions outside of chronological age.